Parents' and Teachers' Perception Patterns of Preschool Children's School Readiness - Nurul Afrianti; Maulida Aulia Rahman; Willya Novianti; Yanti Sam Amir; Eka Sakti Yudha; Euis Kurniati; Solehuddin; Ahman (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This study aims to analyze parents' and teachers' perceptions of the readiness of early childhood education (ECE) schools during the transition period from ECE to elementary school (ES). The approach is descriptive and quantitative, with correlation analysis. The research population consists of parents of ECE and first-grade elementary school students, as well as ECE and first-grade elementary school teachers in Bandung City, West Java. Data were collected from 364 parents and 112 teachers. The research instrument is a Likert-scale questionnaire (1-5) covering aspects of child readiness, parent readiness, teacher roles, home routines, and school communication. Data analysis includes frequency distributions, percentages, means, standard deviations, distribution patterns, and skewness. The analysis results show an average (M) parent perception of 4.0 with a standard deviation of 0.87, and an average teacher perception of 4.31 with a standard deviation of 0.61. There are significant relationships of 0.81 between child readiness and parent readiness, and of 0.74 between parent readiness and perceptions of teacher roles. These findings emphasize the importance of collaboration between parents and schools in supporting children's school readiness.